Digital Transition by COVID‐19 Pandemic? The German Food Online Retail - Dannenberg, Peter (Tijdschr Econ Soc Geogr, 2020)
The COVID‐19 pandemic has led to a sharp increase in online trade. This article examines the impact of the pandemic on online grocery retail in Germany. Here we follow and refine the multi‐level perspective by Geels, and examine to what extent and why the online grocery retail expanded during the pandemic. A particular focus is on the spatial expansion into rural areas. The study shows a general upswing in the grocery trade and disproportionately high growth in online grocery trade and identifies driving and limiting factors. While COVID‐19 has opened a window of opportunity, our results indicate little transition of grocery to e‐grocery. This finding can be explained by the sudden and temporary constellation at the level of the socio‐technical regime during the pandemic. As a result, we argue for a rethinking the temporality of windows of opportunities and the related vulnerability of the innovations which need them.